Gastrodin Ameliorates Motor Learning Deficits Through Preserving Cerebellar Long-Term Depression Pathways in Diabetic Rats - Deng, Cheng-Kun; Mu, Zhi-Hao; Miao, Yi-He; Liu, Yi-Dan; Zhou, Lei; Huang, Yong-Jie; Zhang, Fan; Wang, Yao-Yi; Yang, Zhi-Hong; Qian, Zhong-Yi; Wang, Xie; Guo, Jia-Zhi; et al. (Frontiers in Neuroscience, 2019)
Cognitive dysfunction is a very severe consequence of diabetes, but the underlying causes are still unclear. Recently, cerebellum was reported to play an important role in learning and memory. Since long-term depression (LTD) is a primary cellular mechanism for cerebellar motor learning, we aimed to explore the role of cerebellar LTD pathways in diabetic rats and the therapeutic effect of gastrodin. Diabetes was induced by a single injection of streptozotocin into adult Sprague-Dawley rats. Motor learning ability was assessed by beam walk test. Pathological changes of the cerebellum were assessed by Hematoxylin-Eosin (HE) and Nissl staining. Cellular apoptosis was assessed by anti-caspase-3 immunostaining. Protein expression levels of LTD pathways related factors, including GluR2, PKC, NR2A and nNOS, in the cerebellar cortex were evaluated by western blotting and double immunofluorescence. NO concentration was measured. Cellular degeneration and apoptosis of Purkinje cells were evident in the cerebellum of diabetic rats. Protein expression levels of GluR2 (NC9W: 1.26 ± 0.12; DM9W+S: 0.81±0.07), PKC (NC9W: 1.66 ± 0.10; DM9W+S: 0.58±0.19), NR2A (NC9W: 1.40 ± 0.05; DM9W+S: 0.63±0.06), nNOS (NC9W: 1.26 ± 0.12; DM9W+S: 0.68±0.04) and NO (NC9W: 135.61 ± 31.91; DM9W+S: 64.06±24.01) in the cerebellum were significantly decreased in diabetic rats. Following gastrodin intervention, outcome of motor learning ability was significantly improved (NC9W: 6.70 ± 3.31; DM9W+S: 20.47±9.43; DM9W+G: 16.04±7.10). In addition, degeneration and apoptosis were ameliorated, coupled with elevation of the protein expression of the above-mentioned biomarkers. Arising from the above, we concluded that gastrodin may contribute to the improvement of motor learning through protecting the LTD pathways in Purkinje cells.